Análise espaço-temporal dos impactos socioambientais com o crescimento imobiliário nas margens da Avenida Hélio Gueiros no Bairro do Quarenta Horas - SOUZA, Marco André Novais de (2024)
This study aims to understand how real estate developments affect the environment of the Quarenta Horas neighborhood within the municipality of Ananindeua, Pará. It investigates whether these developments have had and continue to have a negative impact on both the environment and the local population. This research will be supported by the concepts of Environment, environmental impact, Territory, and Gentrification. The latter seeks to examine whether the current urbanization process in the neighborhood is an attempt to "upgrade" the area. The adopted methodology is based on a review of relevant literature and documents, field research for collecting data and information to enrich the article, and the development of cartographic products in the laboratory to provide a comprehensive understanding of the events and the geographical space studied. The expected result is to highlight the expansion of the real estate market as one of the main causes of socio-environmental issues in the neighborhood.